Indeterminacy by underspecification - Dalrymple, M; King, T; Sadler, L (Cambridge University Press, 2009)
We examine the formal encoding of feature indeterminacy, focussing on case in-determinacy as an exemplar of the phenomenon. Forms that are indeterminately specified for the value of a feature can simulataneously satisfy conflicting requirements on that feature and thus are a challenge to constraint-based fomalisms which model the compatibility of information carried by linguistic items by combining or integrating that information. Much previous work in constraint-based formalisms has sought to provide an analysis of feature indeterminacy by departing in some way from 'vanilla' assumptions either about feature representations or about how compatibility is checked by integrating information from various sources. In the present contribution we argue instead that a solution to the range of issues posed by feature indeterminacy can be provided in a 'vanilla' feature-based approach which is formally simple, does not postulate special structures or objects in the representation of case or other indeterminate features, and requires no special provision for the analysis of coordination. We view the value of an indeterminate feature such as CASE as a complex and possibly underspecified feature structure. Our approach correctly allows for incremental and monotonic refinement of case requirements in particular contexts. It used only atomic boolean-valued features and requires no special mechanisms or additional assumptions in the treatment of coordination or other phenomena to handle indeterminacy. Our account covers the behaviour of both indeterminate arguments and indeterminate predicates, that is, predicates placing indeterminate requirements on their arguments.